Assessment of rural development plan measures in Greece. (2017) - Manos, Basil; Bournaris, Thomas; Moulogianni, Christina; Kiomourtzi, Fedra
The rural development plan measures of Common Agricultural Policy affect people living in rural areas and have impacts on agricultural income and rural employment. This paper aims to assess the economic, environmental and social impacts of the 'setting up young farmers' measure of the rural development plan in the region of Central Macedonia in Northern Greece. For this reason, a sample of young farmers who have participated in the 'setting up young farmers' measure was selected. For the impact assessment and the simulation of the results, the knowledge brokerage approach was used along with multicriteria analysis. The results show that the 'setting up young farmers' measure achieved its goal to transfer land to young trained farmers when they started farm business whereas the economic, environmental and social impacts vary between the seven prefectures of the region.